Synthesis of the Hexasaccharide Repeating Unit Corresponding to the Cell Wall O-Antigen of Providencia alcalifaciens O9:H8 Strain - Rana, Abhijit; Misra, Anup Kumar (Synthesis, 2023)
A straightforward synthesis of the hexasaccharide repeating unit of the O-specific polysaccharide of Providencia alcalifaciens O9:H8 strain was achieved in very good yield by applying a stereo- and regioselective [4+2] block glycosylation strategy. The tetrasaccharide acceptor and disaccharide donor were synthesized by sequential stereo- and regioselective glycosylations. Thioglycoside and glycosyl trichloroacetimidate derivatives were used as glycosyl donors in the synthetic strategy. The glycosylation steps were high-yielding and gave satisfactory stereochemical outcomes.
Keywords: carbohydrates; glycosylation; glycoside; oligosaccharide; synthesis